Pentahelix Communication Model in Sustainable Village Development: A Study on Waste Management in Trangsan Village - artiar, Umda Garit; Triyono, Agus (Jogjakarta Communication Conference (JCC), 2025)
The purpose of this study is to explore the involvement of the role of the Five Elements in sustainable village development in the Pentahelix model communication concept in waste management in Trangsan village. The research method used is descriptive qualitative, with data collection techniques through interviews, FGDs, observations and documentation. The result of this study shows that the role of the five elements in the Pentahelix concept has advantages in each dimension such as the government as a policy maker, the business world as a facilitator, academics as coordinators, the community as implementers, and the media as an accelerator and information publication. The sustainable development process requires good communication between individuals and groups to optimize their respective roles and jointly contribute to efforts to improve the quality of life of the community. Thus, the Penta Helix model of sustainable village development strategy can be an effective model for realizing Sustainable Trangsan Village.